The Existence of Indonesian Jewelry: Modern and Contemporary Styles based on the Intuition of the Creation of Traditional Ideas - Setiawan, Deni; Syarif, Muh. Ibnan; Hidayat, Arif; Oktavilia, Shanty; Yustana, Prima; Rahmadani, Ni Kadek Aris (Journal of Ecohumanism, 2024)
This article explores the significance of the jewelry-making tradition in Indonesia and its evolution over time, based on the unique techniques, materials, designs, and varieties of ornaments that make Indonesian jewelry famous locally and internationally. This article aims to analyze jewelry that can have an economic impact based on the local community’s culture and its potential for sustainable development in the region. The research method used was qualitative descriptive, and it was in Jepara, Jombang, Tulungagung, Mojokerto, Ciamis, and Garut in Indonesia, with 30 respondents (artisan groups). Data collection will be done through observation and in-depth interviews to analyze jewelry designs and ornamental varieties—data analysis will be done using the source triangulation technique. The study results show the symbolism and cultural significance of Indonesian jewelry design sourced from traditional values. The source of creation is from the surrounding nature, in the form of plants, streams, branches, and leaves that develop in Indonesia. By combining traditional craftsmanship and ideas with modern marketing and distribution channels, jewelry in Indonesia has survived to this day.